Livelihood Strategy of Coastal Women to Fishermen Family Income - Nur Laila, Nina Evi; Amanah, Siti (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2015)
The livelihoods of fishery households are highly vulnerable to fishery sources due to their nature-depending catchments, fishery households in SendangBiru coastal for example. This study focused to analyse the livelihood strategy and contribution of coastal women in SendangBiru to improve their family income. Descriptive and explanatory methods using questionnaire instrument and purposive sampling were used. The responden samples are coastal women who were productively doing activities to obtain extra income for their family. Coastal women of SendangBiru have important roles to improve their family income by spending a lot of time to do productive and reproductive activities. Coastal women’s income contributions bring about significant effects on fishery families’ financial security. Most of coastal women contributions meet half of their family needs.Keywords: livelihood strategy, coastal women, income contribution, family income